The Differential Expression of ERAP1/ERAP2 and Immune Cell Activation in Pre-eclampsia - Seamon, Kimberly; Kurlak, Lesia O.; Warthan, Michelle; Stratikos, Efstratios; Strauss, Jerome F.; Mistry, Hiten D.; Lee, Eun D. (Frontiers in Immunology, 2020)
Pre-eclampsia (PE) is a disorder of pregnancy, often leading to serious and fatal complications. Endoplasmic reticulum aminopeptidase 1 and 2 (ERAP1/ERAP2) are present in placenta. They are involved in processes regulating blood pressure, angiogenesis, cytokine receptors shedding, and immune recognition. Previous studies have associated both ERAP1/2 genetic variants with PE, although the underlying mechanisms remain unknown. Less is known about the roles for these enzymes in early placentation, which could be a contributory factor to PE. To ascertain whether ERAP1/2 change in PE and whether such a change is present before PE is clinically diagnosed, we analyzed mRNA and ERAP1/2 protein expression in the placenta in early first trimester (8-14 weeks) and at delivery in normotensive or PE women (n=12/group). Gene expression was analyzed using qPCR and protein expression/localization were assessed by immunohistochemistry. Additionally, we profiled peripheral immune cells from normotensive and PE (n=5/group) women for activation and expression of cytotoxic markers using flow cytometry to investigate possible correlation with placental expression of ERAP1/2. Finally, we characterized the cytokines released from immune cells isolated from normotensive women and those with PE, stimulated ex vivo by JEG-3 trophoblast cells. The ERAP1 protein was significantly up-regulated in first trimester placentae compared to placentae at delivery from both normotensive and PE women (p<0.05): expression of placental ERAP1 protein was also relatively higher in normotensive than PE women. Although, protein expression of both ERAP1 and 2 was significantly lower in women with PE compared to normotensive controls (p<0.05), ERAP2 protein expression remained unchanged in normotensive women at delivery compared to expression in the first trimester. Flow cytometry analysis revealed an increase in activation and cytotoxic NK cells in peripheral blood of PE compared to normotensive women. Intriguingly, there was a notable difference in cytokine release from the activated immune cells when further stimulated by trophoblast cells. The immune cells from PE released elevated expression of IL-2, IL-4, and most notably, pro-inflammatory IL-13 and IL-17, inflammatory cytokines TNF- and IFN-, lastly colony stimulating factor GM-CSF compared to normal PBMC. Taken together, these findings suggest that differential lymphocyte activation could be associated with altered ERAP1/2 expression.